Efektivitas Implementasi Program Pilar Indobara untuk Peningkatan Kinerja SHE di PT Putra Perkasa Abadi Jobsite Borneo Indobara - Muhammad Osaegi Restu Amrulloh; Rochmad Choirul Muachor; Zinedina Salsabila Mustain (Master Manajemen, 2025)
The mining sector in Indonesia inherently involves high OSH (Occupational Safety and Health) and Environmental risks, necessitating strict adherence to regulations like Ministerial Decree of Energy and Mineral Resources No. 1827/2018 and Directorate General of Mineral and Coal Decree No. 185/2019. PT Putra Perkasa Abadi (PPA) at the Borneo Indobara Site launched the Indobara Pillar Program to optimize SHE (Safety, Health, Environment) performance and achieve "gold category" status. This research aims to analyze the effectiveness of the program's implementation from February to June 2024, and to identify its supporting and hindering factors. As a case study, this research will describe the implementation process, evaluate target achievement, and analyze influencing factors. Despite the program's launch, January 2024 data showed initial challenges: 67% overall program achievement, with only 38% of programs being effective. Key issues included inconsistent monitoring, unsuitable forms, poor synchronization of internal leading indicator data, insufficient understanding among SHE Group Leaders, and suboptimal personal safety awareness. These challenges directly impacted SHE performance targets. In conclusion, this in-depth analysis is expected to identify how the Indobara Pillar Program can be optimized, contribute to OSH/SHE literature, and enhance the company's safety culture comprehensively.